Receipt of vaginal brachytherapy is associated with improved survival in women with stage I endometrioid adenocarcinoma of the uterus: A National Cancer Data Base study. Issue 23 (10th August 2016) - Rydzewski, Nicholas R.; Strohl, Anna E.; Donnelly, Eric D.; Kanis, Margaux J.; Lurain, John R.; Nieves‐Neira, Wilberto; Strauss, Jonathan B.
Abstract : BACKGROUND: Randomized controlled trials have consistently shown that the use of postoperative radiotherapy (RT) for stage I endometrial cancer leads to a reduction in the incidence of pelvic recurrences without a corresponding reduction in overall mortality. It was hypothesized that a reduction in mortality associated with the receipt of RT could be identified in a large data set with greater statistical power. METHODS: Women with surgically staged IA or IB endometrial adenocarcinoma who were treated with total hysterectomy between 2003 and 2011 were identified in the National Cancer Data Base. Chi‐square tests and multivariate logistic regression were performed to analyze factors associated with the treatment type. A survival analysis was performed with log‐rank testing, Cox proportional hazards regression, and Kaplan‐Meier estimates. RESULTS: A total of 44, 309 eligible women were identified (33, 380 at stage IA and 10, 929 at stage IB): 88.4% of the women with stage IA tumors and 51.6% of the women with stage IB tumors received no RT. Older age, comorbid disease, a higher histologic grade, and a larger tumor size were independently associated with an increase in mortality. The receipt of vaginal brachytherapy (VB) was independently associated with a reduction in mortality for both stage IA disease (hazard ratio [HR], 0.81; 95% confidence interval [CI], 0.67‐0.97) and stage IB disease (HR, 0.62; 95% CI, 0.51‐0.74). CONCLUSIONS: Analyses of this large database support the utility of postoperative VB for many women with stage I endometrial cancer. Unfortunately, RT appears to be underused in this population. Greater adherence to consensus guidelines may lead to improved outcomes. Cancer 2016;122:3724‐31. © 2016 American Cancer Society . Abstract : Analyses from the National Cancer Data Base support the utility of postoperative vaginal brachytherapy for many women with stage I endometrial cancer. Unfortunately, radiotherapy appears to be underused in this population, but greater adherence to consensus guidelines may lead to improved outcomes.